Analisis Pengelolaan Perpustakaan dalam Mendukung Literasi Siswa di SMA N 1 Ngawi - Mohammad Ardiansyah Avilianto; Reka Nur Azizah Pratina; Mitha Widyastuti (Universitas PGRI Madiun, 2026)
This study aims to analyze library management in supporting student literacy at SMA Negeri 1 Ngawi. Effective library management is an important factor in improving literacy culture in the school environment through the provision of collections, services, facilities, and infrastructure, as well as sustainable literacy programs. This study uses a qualitative approach with a descriptive research type. Data were obtained through observation, interviews, and documentation involving the head of the library, librarians, teachers, and students. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results show that library management at SMA Negeri 1 Ngawi has been implemented through the functions of planning, organizing, implementing, and monitoring. The library provides various print and digital collections, circulation services, and activities that support students' reading culture. However, several obstacles remain, such as limited collection development according to user needs, suboptimal use of information technology, and low frequency of visits by some students. Therefore, it is necessary to increase service innovation, optimize information technology, and strengthen collaboration between the library, teachers, and the school so that the library can play a more optimal role in supporting student literacy. This study concludes that good library management makes a positive contribution to improving student literacy at SMA Negeri 1 Ngawi.